Authority Defied: Need for Cognitive Closure Influences Regulatory Control When Resisting Authority. Issue 4 (26th August 2013) - Damen, Tom G. E.; van Leeuwen, Matthijs L.; Dijksterhuis, Ap; van Baaren, Rick B.
Abstract The present studies examined whether differences in need for cognitive closure (NCC) were related to differences in regulatory control when confronted with authority. In two studies, levels of regulatory control were measured when participants resisted (Study 1; N = 46) or prepared to resist the influence attempt of an authority figure (Study 2; N = 50). Results showed that resisting the influence attempt from a high‐authority figure was more depleting for participants higher in NCC compared to individuals lower in NCC. However, when they were given instructions and time to prepare the act of resistance, individuals high in NCC actually showed an increase in regulatory control. Authority is usually viewed as a general principle of influence; however, the present studies suggest that there are individual differences that influence how people may experience interactions with authorities.